A Quantitative Method for Simultaneous Determination of 5-Methoxy-N,N-Diisopropyltryptamine and its Metabolites in Urine Using Liquid Chromatography-Electrospray Ionization-Tandem Mass Spectrometry - Jin, Ming J.; Jin, Changbae; Kim, Jin Y.; In, Moon K.; Kwon, Oh S.; Yoo, Hye H. (WILEY, 2011)
5-Methoxy-N,N-diisopropyltryptamine (5-MeO-DIPT) is a designer hallucinogen derived from tryptamine and is reportedly abused and involved in criminal activities. For the detection of 5-MeO-DIPT use, a liquid chromatography-tandem mass spectrometric method for 5-MeO-DIPT and its metabolites, 5-hydroxy-N,N-diisopropyltryptamine (5-OH-DIPT) and 5-methoxy-N,N-isopropyltryptamine (5-MeO-IPT) was developed and validated in rat urine. The urine samples were pretreated by protein precipitation with acetonitrile and introduced into a BDS HYPERSIL C-18 column (50 x 2.0 mm, 5 mu m) for chromatographic separation. Mobile phases consisted of methanol, water, and 1% formic acid, and gradient elution was used at a flow rate of 0.2 mL/min. For the MS detection, multiple-reaction monitoring analysis was adopted. The linear range was 0.01-10 mu g/mL, and the lower limit of quantification was 10 ng/mL for all analytes. The intra- and interday accuracies and precisions met the criteria (< 15%). The developed method was successfully applied to the drug-treated rat urine.